S171. Intra operative neurophysiological evoked potentials in patients with spinal muscular atrophy undergoing spine deformity corrective surgery: A retrospective, single-center experience. (May 2018) - Tewari, Anurag; Busso, Veronica; Castle, Joshua; Taylor, Teal; Schaiper, Lindsy; Frye, Tiffany
Abstract : Introduction: Patients with spinal muscular atrophy are a difficult population for neurophysiological monitoring. In our retrospective study, we attempt to study the characteristics of the evoked potentials and their physiognomies in three types of phenotypes, which present for surgical correction of their spine deformity. Methods: A retrospective IONM database review was accomplished for ten patients who underwent 35 surgeries at our institution from August 2010 till March 2015. TcMEPs, SSEPs, free running EMG, EEG, and TOF, were recorded in all cases after the patients were anesthetized. Recordings were measure before and after positioning and throughout the surgical procedure. Results: In the patients identified, intraoperative monitoring records were analyzed for characteristics of IONM modalities commonly used. In 34 (97.14%) surgeries, patients had obtainable and reproducible upper SSEPs. Lower limb SSEPs were present and were within normal range in 17 (48.57%) procedures. In eight cases (13%), no reliable monitoring could be achieved and was therefore abandoned. Right brevis TcMEPs was absent in one (2.84%), while it was obtained in all other cases. While potentials from hallicus and tibialis anterior were absent in only seven cases (20%). Throughout the surgery, there was no statistically significant variation in the depth of anesthesia as measured by the spectral index of the EEG ( p = 0.4849). Conclusion: We conclude that SSEPs and TcMEPs are obtainable and could be combined with other routine IONM modalities to monitor SMA patients undergoing spine corrective surgeries. The presence of upper extremity SSEP and TcMEPs enable perioperative monitoring to mitigate any impending neurological injuries, especially to the brachial plexus.